Um olhar sobre o luxo : representações, significados e práticas entre um grupo de jovens moradores da Rocinha - Cruz, Daniela Jacques da (2018)
The research “A look at luxury: representations, significances and practices among a group of young people living in Rocinha” analyzes the main representations of luxury among a youth group living in Rocinha, a slum in the city of Rio de Janeiro. The research proposes an investigation based on an anthropological approach that understands luxury and its consumption as something active, usual and part of daily life. Luxury is interpreted from a perspective that contemplates symbolic and practical aspects, in which it fulfils a role of creating structured values: it builds identities, regulates social relations and defines cultural maps. Ethnography was the methodology that guided the research, with the use of observant participation and indepth interviewing; netnography was also used, with the analysis of postings by the researched youths on the main social media: Instagram and Facebook. The overall objective of this research is to understand how practices, significances and representations of luxury are constructed in the realm of consumption among a group of young residents in Rocinha. In addition to representations, significances and practices of the researched youths related to luxury, the outcomes reveal the specificity of being a slum dweller, because regardless of their production, creation and consumption, they still feel themselves seen by society in a stigmatized way and they see in education and knowledge the path to remove the stigma of being a slum dweller.